INFLUENCE OF EDAPHIC VARIABLES ON PREDOMINANCE OF FOREST SPECIES AFTER SELECTIVE LOGGING IN THE AMAZONIAN BIOME (Nativa, 2024)
ABSTRACT: The floristic composition of fragmented landscapes can significantly influence their potential resilience and regeneration in the event of natural or anthropogenic disturbance. This study aimed to characterize soil influence on tree composition and determine the relationship of edaphic variables to the predominant species in a part of the Amazon Forest under selective logging. The fixed area method was applied to clusters of 10 × 250 m, considering trees with a DBH ≥ 10 cm. The 20 highest-importance species of the fragment composed the vegetation matrix. For the characterization of the forest soil, three soil samples composed of subunits were collected, and the edaphic variables were represented by pH H2O, pH CaCl2, P, K, Ca, Ca+Mg, Mg, Al, H, OM, SB, CEC, V%, Ca%, Mg% and TOC. Despite the low tree density found in the study, the high basal area suggests that the species present are tolerant to changes and environmental disturbances. The tree component is dominated by species characteristic of degraded environments, where the soil’s chemical composition explains most of the species variation. Qualea paraensis, Bellucia grossularioides, Cheiloclinium cognatum, Diplotropis purpurea and Erisma uncinatum show great potential for use in degraded forest ecosystems in the Amazon Biome.Keywords: anthropic disruption; deforestation; ecological requirements; forest ecosystem recovery; tropical rainforest. Influência das variáveis edáficas na predominância de espécies florestais após exploração seletiva no bioma amazônico RESUMO: A composição florística de paisagens fragmentadas pode influenciar significativamente o seu potencial de resiliência e regeneração em caso de perturbação natural ou antropogénica. O objetivo deste trabalho foi caracterizar a influencia do solo na composição arbórea e determinar a relação das variáveis edáficas com as espécies predominantes em uma parte da Floresta Amazônica sob exploração madeireira seletiva. O método de área fixa foi aplicado para aglomerados de 10 X 250 m, considerando arvores com DAP ≥ 10 cm. As 20 espécies de maior importância do fragmento compuseram a matriz vegetal. Para a caracterização do solo florestal foram coletadas três amostras de solo compostas por subunidades e as variáveis edáficas foram representadas por pHH2O, pHCaCl2, P, K, Ca, Ca+Mg, Mg, Al, H, OM, SB, CEC, V%, Ca%, Mg%, e TOC. Apesar da baixa densidade arbórea encontrada no estudo, a elevada área basal sugere que as espécies presentes são tolerantes a mudanças e pertubações ambientais. O componente arbóreo é dominado por espécies características de ambientes degradados, onde a composição química do solo explica a maior parte da variação das espécies. As espécies Qualea paraensis, Bellucia grossularioides, Cheiloclinium cognatum, Diplotropis purpurea e Erisma uncinatum apresentam grande potencial para utilização em ecossistemas florestais degradados na Amazónia.Palavras-chave: perturbação antrópica; desmatamento; requerimentos ecológicos; recuperação do ecossistema florestal; floresta tropical.